ISLAM DAN PANCASILA DALAM PEMIKIRAN MOHAMMAD NATSIR - Mhd Alfahjri Sukri (Alfuad: Jurnal Sosial Keagamaan, 2019)
This research was conducted to see how Mohammad Natsir thought about the relationship between Islam and Pancasila. This study also explains the causes of Natsir's change of mind which initially supported Pancasila as part of Islam and later turned into an opponent of Pancasila in Konstituante on 11 November to 6 December 1957. The methodology used was a qualitative method by describing the results of the analysis carried out. The research data is obtained through a review of documents and scientific literature. The results of the study show that Mohammad Natsir's change of mind regarding the relationship between Islam and Pancasila was influenced by Mohammad Natsir's political socialization which began from Natsir's view of Islam influenced by the childhood environment (conditional and socio-cultural) in Minangkabau; direct influence from national figures such as Ahmad Hassan, H. Agus Salim, Sheikh Ahmad Syurkati and H. O Tjokroaminoto; the indirect influence of international figures throughout reading book such as Hassan Al-Banna, Amir Syakib Arselan, Rashid Ridha and Muhammad Abduh; the influence of Natsir's organization and political parties, namely Jong Islamieten Bond (JIB), Islamic Unity (Persis), and Masyumi political parties; and the influence of the political conditions at that time which made Natsir's views change, which initially accepted Pancasila and then became an opponent of the Pancasila. This research shown there are two patterns of Natsir's relationship with Pancasila, namely (1) Natsir accepted Pancasila and, (2) Natsir opposed Pancasila.